THE EXPERIENCE OF ORGANIZING COLLABORATIVE WORK OF ORENBURG BRANCH OF S. FYODOROV EYE MICROSURGERY FEDERAL STATE INSTITUTION AND ORENBURG REGIONAL PERINATAL CENTRE FOR THE CONTROL OF RETINOPATHY OF PREMATURITY - A. D. Chuprov; E. K. Malgina (Сибирский научный медицинский журнал, 2019)
The purpose of the study is to increase the efficiency of delivering high-tech eye care to the infants of Orenburg and the Orenburg region.Material and methods. An algorithm has been developed to deliver specialized care for retinopathy of prematurity. Recently purchased «RetCam3» pediatric retinal camera made it possible to conduct dynamic screening and monitoring of preterm infants who were prematurely born at risk of retinopathy. The examination was prescribed to children at risk (gestation age up to 35 weeks, birth weight up to 2500 g). The time frame for fundoscopy varied from 3 to 7 weeks after birth depending on the infant physical condition. The number of examinations at 3th–4th weeks of life was 63 %, at 5th–6th weeks – 29 %, at 6th–7th weeks – 8 %. Screening examinations were carried out in the perinatal centre with intervals, depending on the stage of retinopathy of prematurity: preretinopathy, stage I and II from 1 to 2 weeks, III and more severe stages from several days to a week. 60 initial examinations were performed in 6 months, laser treatment was provided for 13 patients (21.7 %).Results and discussion. For 6 months, 60 initial examinations were performed; laser treatment was performed in 13 patients (21.7 %). We observed positive changes for all the infants after laser treatment, which proves high efficiency of the developed algorithm of treatment premature infants with retinopathy, which is the prevention of blindness and low vision from infancy. Repeated monitoring after laser coagulation was carried out after 2, 4 and 8 weeks.Conclusions. Thus, screening contributes to the identification of this pathology at an early stage, dynamic monitoring of the fundus changes is carried out using retinal camera, which contributes to timely laser treatment. The developed algorithm improves the quality of specialty care for premature infants at risk of developing retinopathy of prematurity, and, accordingly, improves the quality of their life.